(untitled) (Comparatismi, 2023)
Since the last decades of the 20th century, there has been a growing interest in the study of emotions. The emotional turn (T. Anz 1999) has not only involved psychology (K. Oatley 2004, P. Ekman 2003, K. Scherer 2009) but is a true interdisciplinary approach (Affective Sciences). The sense of guilt, first studied in psychology by Freud in Mourning and Melancholy (1917), is a complex secondary emotion (C. Izard 1977) that is generated by the relationship with society and its norms and is therefore defined as self-reflexive, for it implies that the individual reflects on him/herself within his/her social context. In Vous serez mes témoins (2011), the French-Hungarian writer Nina Yargekov approaches the theme of the sense of guilt over the suicide death of her best friend Élodie. Balancing between a court testimony and a diary of mourning, the novel tells the story of a court trial where the narrator is accused of an unusual fraud: the simulation of mourning. The novel becomes simultaneously the courthouse and the diary in which to record the sense of guilt in a neurotic and chaotic manner. A painful writing full of fiction and humour, which thanks to the skilful use of parody and pastiche makes possible the literary transposition of what can hardly be said and understood.